2018
DOI: 10.2134/agronj2018.03.0148
|View full text |Cite
|
Sign up to set email alerts
|

Combining Trinexapac‐Ethyl with a Soil Surfactant Reduces Bermudagrass Irrigation Requirements

Abstract: Core Ideas We describe the use of a plant growth regulator and a soil surfactant for water conservation. We investigated whether the beneficial effects of a surfactant and a plant growth regulator on drought stressed bermudagrass were enhanced when applied in combination versus individually. We investigated if both products affect soil moisture under reduced irrigation. Soil surfactants and plant growth regulators (PGR) have shown potential to lower irrigation requirements and increase turfgrass quality under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…Soil surfactants, otherwise called “wetting agents,” such as Revolution (modified methyl capped block copolymer; Aquatrols, Paulsboro, NJ), have been commonly used to prevent localized dry spots and to increase visual quality under drought conditions (Karnok et al, 2004; Kostka, 2000; Kostka et al, 2007). It has been recently shown that Revolution improves soil moisture uniformity, especially when DI is used to irrigate turfgrass (Schiavon et al, 2014a, 2014b; Serena et al, 2018a). Moreover, Serena et al (2018a) demonstrated that the use of TE in combination with a surfactant not only improved ‘Princess 77’ bermudagrass performance but also helped sustain sufficient visual quality when irrigated at 50% ET o .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Soil surfactants, otherwise called “wetting agents,” such as Revolution (modified methyl capped block copolymer; Aquatrols, Paulsboro, NJ), have been commonly used to prevent localized dry spots and to increase visual quality under drought conditions (Karnok et al, 2004; Kostka, 2000; Kostka et al, 2007). It has been recently shown that Revolution improves soil moisture uniformity, especially when DI is used to irrigate turfgrass (Schiavon et al, 2014a, 2014b; Serena et al, 2018a). Moreover, Serena et al (2018a) demonstrated that the use of TE in combination with a surfactant not only improved ‘Princess 77’ bermudagrass performance but also helped sustain sufficient visual quality when irrigated at 50% ET o .…”
mentioning
confidence: 99%
“…It has been recently shown that Revolution improves soil moisture uniformity, especially when DI is used to irrigate turfgrass (Schiavon et al, 2014a, 2014b; Serena et al, 2018a). Moreover, Serena et al (2018a) demonstrated that the use of TE in combination with a surfactant not only improved ‘Princess 77’ bermudagrass performance but also helped sustain sufficient visual quality when irrigated at 50% ET o . Nevertheless, no studies have investigated the combined effect of TE and surfactant using DI on bermudagrass during multiple growing seasons.…”
mentioning
confidence: 99%
“…Additional research is needed to investigate if tank mixing both chemicals would produce a synergistic effect, improving rooting to a greater degree than when each product is applied separately. Serena et al (2018) documented that tank mixing Revolution and TE resulted in greater turf quality and green turf cover of bermudagrass than applying the products alone, but rooting and physiological data were not investigated. More research is also needed to explore the efficacy of TE in combination with reduced irrigation on stolon or rhizome production.…”
Section: Discussionmentioning
confidence: 99%
“…Soil surfactants have been used historically in the turfgrass industry to alleviate soil hydrophobicity and improve infiltration and percolation (Cisar, Willimas, Vicas, & Haydu, 2000; Karnok, Xia, & Tucker, 2004; Kostka & Bially, 2005). More recently, studies have documented the role of surfactants in water conservation (Leinauer & Devitt, 2014; Schiavon, Leinauer, Serena, Maier, & Sallenave, 2014; Serena, Sportelli, Sevostianova, Sallenave, & Leinauer, 2018). Another group of chemicals that are marketed to help conserve water are the PGRs.…”
Section: Introductionmentioning
confidence: 99%
“…Anti‐transpirant applications are used to limit winter desiccation in tree crops (Christiansen & Ashworth, 1978). Soil wetting agents have also been shown to sustain turfgrass quality during summer drought and desiccation stress (Kostka, Cisar, Short, & Mane, 1997; Serena, Sportelli, Sevostianova, Sallenave, & Leinauer, 2018; Soldat, Lowery, & Kussow, 2010). DeBoer, Richardson, McCalla, and Karcher (2019) found that soil wetting agent applications in late fall improved spring green‐up of hybrid bermudagrass ( Cynodon spp.).…”
Section: Introductionmentioning
confidence: 99%